1987
DOI: 10.1111/j.1432-1033.1987.tb10594.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of ADP and orthophosphate during the ATPase reaction of nitrogenase

Abstract: The pre-steady-state ATPase activity of nitrogenase from Azotobucter vinelundii was investigated. By using a rapid-quench technique, it has been demonstrated that with the oxidized nitrogenase complex the same burst reaction of MgATP hydrolysis occurs as observed with the reduced complex, namely 6 -8 mol orthophosphate released/mol MoFe protein. It is concluded that the pre-steady-state ATPase activity is independent of electron transfer from Fe protein to MoFe protein. Results obtained from gel centrifugation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The amounts of Av2, Avl and ADP in the nitrogenase.ADP-A1F~ complex were determined: 2.7 + 0.2 Av2/Avl and 2.0 + 0.2 ADP/Avl were present. Cordewener et al [19] observed that two molecules of MgADP bind to Av2, but that only one MgADP molecule binds very tightly to Av2. The less tightly bound MgADP apparently is not present in the nitrogenase.…”
Section: Characterization Of the Nitrogenase Adp Alf 4 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…The amounts of Av2, Avl and ADP in the nitrogenase.ADP-A1F~ complex were determined: 2.7 + 0.2 Av2/Avl and 2.0 + 0.2 ADP/Avl were present. Cordewener et al [19] observed that two molecules of MgADP bind to Av2, but that only one MgADP molecule binds very tightly to Av2. The less tightly bound MgADP apparently is not present in the nitrogenase.…”
Section: Characterization Of the Nitrogenase Adp Alf 4 Complexmentioning
confidence: 99%
“…Cordewener et al [19] observed that two molecules of MgADP bind to Av2, but that only one MgADP molecule binds very tightly to Av2. The less tightly bound MgADP apparently is not present in the nitrogenase.…”
Section: Characterization Of the Nitrogenase Adp Alf 4 Complexmentioning
confidence: 99%
“…This distance is too large to permit direct chemical coupling of electron transfer and ATP hydrolysis. A close structural similarity has been found between the nucleotide-binding regions of the nitrogenase Fe protein and the H-Ras p21 protein 19,201, which has GTPase activity and of which the MgGTPbinding and MgGDP-binding properties have been well characterized. The nucleotide-binding regions of the Fe protein and the H-Ras p21 protein are different with respect to the orientation of the nucleotide.…”
mentioning
confidence: 94%
“…Cordewener et al [19] have shown that Av2 tightly binds one molecule of MgATP or MgADP. Later it was found that a single ADP molecule co-crystallized with Av2, bound in the interface region between the two subunits, and was separated by approximately 2 nm from the [4Fe-4S] cluster [9].…”
mentioning
confidence: 99%
“…Sequence analysis [10] and the three-dimensional X-ray crystal structure of the Fe protein [11] has revealed a potential nucleotide-binding site on each subunit. However, the hydrolysis of MgATP by nitrogenase requires both the MoFe protein and the Fe protein, although protein-protein electron transfer is not necessarily required, since hydrolysis is catalysed by dye-oxidized proteins [12]. Thus the MgATP-hydrolysing site is generated when the MoFe protein and the Fe proteins form a complex, which has been physically demonstrated by ultracentrifugation studies [13].…”
Section: Introductionmentioning
confidence: 98%